Storytelling Instagram @Ramondaaudii untuk Membangun Brand Equity Wardah - Ni Putu Intan Permatasari; Aprilia Wardani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze how Wardah's brand equity is built through a storytelling strategy implemented by Instagram content creator @ramondaudii. The method used is descriptive qualitative, with data collected through observation, in-depth interviews with the content creator and ten active followers, and document studies. The main findings show that storytelling can utilize the creator's personal experiences, informative visual details and a narrative flow that is highly relevant to the audience's needs. This technique has proven successful in increasing consumer understanding of the benefits of Wardah products while establishing a stronger emotional connection with the brand. The narrative conveyed triggers a positive cognitive response in the audience. This response includes thoughts that support the message, increased brand awareness, better perceptions of product quality and a significant boost to purchasing decisions. This positive response contributes directly to strengthening the four main dimensions of Wardah's brand equity (awareness, brand associations, perceived quality, loyalty). Overall, this study concludes that storytelling is an appropriate communication strategy in expanding market reach and increasing Wardah's appeal, especially in the younger user segment or Generation Z who tend to respond better to narrative content that is considered authentic.